PENGARUH FAKTOR DEMOGRAFI, EKONOMI DAN LINGKUNGAN TERHADAP KEPUTUSAN BERINVESTASI SAHAM DI KOTA DENPASAR - Nainggolan, Ananda Rissa Natasya; Sukadana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p10, 2023)
Portfolio investment is one of the right providers of capital for the stability of the Capital Establishment Balance. Capital providers, namely the capital market as a provider of funds for companies that will have implications for the economy. Stock is one of the right instruments and has been widely known by the public but has not been fully implemented properly. In investing in stocks, there are demographic, economic, and environmental factors that influence one's decision making in investing in stocks. This study aims to analyze the effect of age, gender, income, and environment simultaneously and partially on the decision to invest in shares in Denpasar City. This research was conducted on stock investors in Denpasar City with a total sample of 410 respondents using questionnaires and interview instruments. The data analysis technique used in this research is logit and probit. The results of this study indicate that simultaneously the variables of age, gender, income, and environment affect stock investment decisions in Denpasar City. Partially, the variables that influence stock investment decisions in Denpasar City are age, gender, income, and environmental variables